SECANG (Caesalpinia sappan L.), GAMBIER (Uncaria gambir Robx.) AND PINANG (Arecha catechu L.) AS ALTERNATIVES FOR NATURAL COLOR IN COSMETIC PREPARATIONS - latirah latirah (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2021)
Secang wood (Caesalpinia sappan L.), gambier (Uncaria gambir Robx.) and areca seed (Arecha catechu L.) are alternatives that are used as natural dyes in food and beverages. This research aims to develop extracts of secang wood, gambier and areca seeds as natural dyes in cosmetic preparations. The manufacture is done by making a thick extrack of secang wood, gambier and areca seeds using solvent etanol 96 %. The resulting viscous exctract was evaluated by colour test using by cromameter. The reseach produced secang wood dyes with a volue of 0HUE 23,30±0,100 (red), gambier 338±0,116 (purple) and areca seeds 337,03±1,497 (purple), while the 0HUE value of the combination of thick extracts of secang-gambier 344,03±0,346 (purple red), secang-areca 10,27±0,208 (purple red) and secang-gambier-areca 6,49±0,150 (purple red). Keywords : secang wood, gambier, areca seeds.